A postura corporal e as funções estomatognáticas em crianças respiradoras orais de 8 e 9 anos - Machado, Patrícia Girarde (2011)
The influence of mouth breathing to the adequate performance of the stomatognathic system functions and about the body posture have been discussed in the scientific environment. Mouth breathing is a pathologic condition, whose etiology is multifactorial, being able to be subcategorized as obstructive/organic and functional/vicious. The purpose of this study was to verify the relationship between global body posture and the stomatognathic functions in obstructive and functional oral breathers. For this, we evaluated 21 children, aged between 8 and 9 years old, 8 male and 13 female. We evaluated the structure and functions of the stomatognathic system; of the body posture, through the digital biophotogrammetry, processed by the software SAPo® and otorrinolaringologic, through rhinoscopy and nasofibroscopy. After processing and analyzing the study data, we applied the Chisquare, Fisher, or Mann-Withney Tests, and the Student s t-test, with level of significance of 5% (p < 0.05). We also carried out group analyses or cluster. The proper chewing, that is alternate bilateral, was observed in a higher level in OOB (Obstructive Oral Breathers) (12.5%) compared to VOB (Vicious Oral Breathers) (7.7%). The chewing noise presented a high frequency in both groups (VOB 61.5%; OOB 75%). The OOBs also presented a higher frequency related to the noise and speed alterations. Regarding the other atypical characteristics, the group of VOBs obtained a higher frequency, but the results were not statistically significant. In swallowing, as the normal patterns as the atypical characteristics are more frequent in VOB, except the noise which was the only observed statistical difference in OOBs. In dendograms, anterior and lateral views, as well as in the biophotogrammetry, the head was anteriorized in the groups. We could observe the prevalence of head anterior deviation and the presence of cephalic movements in OB (Oral Breathers) during swallowing (p=0.016) and a longer time of chewing (p=0.047). So, there is no difference if the oral breather is obstructive or vicious, to the harmful effects to the stomatognathic system and to the body posture, as well as the little significant relation between posture and stomatognathic functions. Therefore, it is extremely important that during the evaluation of the stomatognathic functions we consider the way of breathing and the body posture of each individual, because some results were statistically sig nificant.